Knowledge on fall risk factor and practice on fall prevention toward elderly patient among nurses in Hospital Universiti Sains Malaysia (Hospital USM) - Nawi, Nur Syafiqa Mohd (2020)
Fall is defined as an accident that causes a person to unintentionally rest on the ground or floor. Fall has become one of the main health problems as it has been the second leading cause of unintentional injury that leads to death after road traffic injury and fall happen to occur at any place including the hospital. The complication can be serious as traumatic brain injury, hip fracture or even death. Elderly are the most at risk for fall as their physiological process of ageing is related to decline in health, including bone strength, gait and balance problem. Therefore, this study sought to determine knowledge on fall risk factor and practice used in preventing fall in elderly among nurses in Hospital Universiti Sains Malaysia (Hospital USM). This is a cross-sectional study conducted among nurses in the medical and surgical ward. The questionnaire used in the study was a self-administered questionnaire consist of 16 questions regarding fall risk factor and 4 questions on practice in preventing fall. Descriptive statistic has been used to analyze data. There was only 55 respondent involved in this study as the researcher did not happen to be able to achieve the supposed number of sample size due to Covid 19 outbreak. However, based on data collected, the result shows nurses’ level of knowledge on fall risk factor and practice in fall prevention is above the average level. It shows that nurses have good knowledge and practice in handling fall in the ward. For the association between socio-demographic data (working experience, and had attending talk on fall prevention) and knowledge level shows no significant association. There is also no significant association between the level of knowledge and practice altough the result show that nurses with a good level of knowledge have a good level of practice. In conclusion, this study found that most of the nurses know the idea about fall risk factor and preventive measure as their scoring on this matter was at the above average level. Hence, they did a great job and it should be persistent and achieve excellent fall management with zero cases of fall.